Smart Farming in Agriculture (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Smart farming is an emerging approach that integrates advanced technologies to revolutionize traditional agricultural practices. It leverages tools like the Internet of Things (IoT), Artificial Intelligence (AI), drones to improve productivity, sustainability, and decision-making in agriculture. In India, where over 70% of the rural population depends on farming, precision agriculture offers a powerful solution to challenges faced by farmers and also to adopt the climate changes. IoT sensors enable real-time monitoring of soil moisture, weather, and crop health, optimizing irrigation and input use. AI-driven analytics support early detection of pests and diseases and guide farmers on crop management strategies. Smart farming significantly boosts crop yield, reduces resource wastage, and improves market access for farmers. Customized models for small and large landholders ensure affordability and scalability. Real-world implementations like Harita-Priya, AgSpeak, Cropin, and AgriRain have shown measurable success in improving yields and farmer incomes, which was included as uses case in this paper. This paper attempts to address the needs of farmers of below 5 acres and above 5 acres and suggests the smart farming technology required and cost of implementation suits to both categories of farmers groups. As the country advances toward a digital agricultural ecosystem, smart farming will be pivotal for achieving food security and climate resilience and marks the beginning of a transformative era in Indian agriculture, promoting environmental sustainability.